Latent Profiles of Posttraumatic Growth and Their Relation to Differences in Resilience among Only-Child-Lost People in China - Zhang, Wen (PLoS One, 2016)
AIMS: Since the early 1980s, the one-child policy has been implemented nationwide in China. A special group called the “only-child-lost family” (OCL family) has emerged and has become a social phenomenon that cannot be ignored. We report latent profiles of posttraumatic growth and their relation to differences in resilience among OCL people in China. METHODS: A total of 222 OCL people were investigated using the Posttraumatic Growth Inventory and the Connor-Davidson Resilience Scale. Latent profile analysis was applied to explore PTG latent profiles. Multinomial logistic regression was used to analyze the socio-demographic variables in each latent profile and the association between profile membership and resilience. RESULTS: Three latent profiles were identified and labeled the “high appreciation-power group” (30.6%), the “general moderate growth group” (47.7%) and the “low growth and extreme possibility group” (21.7%). Compared to those in the high appreciation-power group, individuals with monthly income >2000 ($312) were less likely to be in the general moderate growth group (OR = 0.13, P<0.01), whereas individuals with a spouse were less likely to be in the low growth and extreme possibility group (OR = 0.43, P<0.01). Individuals in the “general moderate growth group”(OR = 0.92, P<0.01, 95%CI:0.89–0.94) and the “low growth and extreme possibility” groups (OR = 0.83, P<0.01, 95%CI:0.79–0.87) demonstrated significantly lower levels of resilience compared to the high appreciation-power group. CONCLUSION: The PTG patterns in only-child-lost parents were varied. Promoting resilience may be a way to foster these parents’ PTG. Targeted intervention should be developed based on the characteristics of each latent class, and timely attention must be paid to the mental health of OCL parents who are without a spouse and have low income.